Islamic Study On The Law Of Husbands Forcing Wives To Have Abortions Due To Economic Factors - Vick Ainun Haq; Adella Dewi Nur’aini; Amirudin Amirudin (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This article aims to strengthen the ruling on the law of husbands forcing their wives to have abortions due to economic reasons. So far, abortion has always been considered to be something that is always blamed in law and religion, when in fact humans have the right to have an abortion legally, according to the reasons that support it. This type of research uses qualitative, with a literature review approach where the data collected by researchers are taken based on primary and secondary sources. Primary sources are related to the topic of abortion and the thoughts of Al Ghazali and Yusuf Qardawi about abortion, while secondary based on previous studies relevant to the theme. The analysis technique used is content analysis, with descriptive-analysis method. The results of this study indicate that (1) When viewed from Maqashid Sharia Al Ghazali that the law of abortion due to economic factors is haram, while (2) When reviewing the concept of emergency Yusuf Qardawi that abortion due to economic factors is permissible but not more than 40 days of gestation, with the author's analysis that Yusuf Qardawi allows for reasons of common benefit, because poverty (economic factors) is prone to be a factor of crime against society, such as theft, robbery and even murder.